2011
DOI: 10.1007/s10103-011-1008-9
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy improves repair following complete resection of the sciatic nerve in rats

Abstract: The aim of this study is to analyze the effects of low-level laser therapy (LLLT) on the regeneration of the sciatic nerve in rats following a complete nerve resection. Male Wistar rats were divided into a control injury group, injury groups irradiated with a 660-nm laser at 10 or 50 J/cm(2), and injury groups irradiated with an 808-nm laser at 10 or 50 J/cm(2). Treatment began 24 h following nerve resection and continued for 15 days. Using the sciatic functional index (SFI), we show that the injured animals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 19 publications
1
25
0
9
Order By: Relevance
“…The laser has biostimulator effect on peripheral nerve repair, as it helps to improve blood supply, cell proliferation and collagen synthesis. In addition, the therapy provides analgesic, anti-inflammatory and anti-edema effects [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The laser has biostimulator effect on peripheral nerve repair, as it helps to improve blood supply, cell proliferation and collagen synthesis. In addition, the therapy provides analgesic, anti-inflammatory and anti-edema effects [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have also reported positive effects for LLLT in improving neuropathic pain, promoting functional recovery of peripheral nerves, and accelerating axonal growth and regeneration [20][21][22][23]. It has been recommended that LLLT should be started as soon as possible during the acute phase of nerve injury, due to its modulatory actions on inflammation [24].…”
Section: Introductionmentioning
confidence: 97%
“…4 The regenerative responses of the axon under photobiomodulatory doses of light, 5 most commonly at 810 nm in studies performed on rodent models, [6][7][8] are particularly promising for treating spinal cord diseases that are difficult to access anatomically and therapeutically. However, in spite of the obvious potential for the treatment regimen, PBMT for spinal cord disease remains clinically untested.…”
Section: Introductionmentioning
confidence: 99%